Vaccination with a fowl adenovirus chimeric fiber protein (crecFib-4/11) simultaneously protects chickens against hepatitis-hydropericardium syndrome (HHS) and inclusion body hepatitis (IBH). Issue 12 (15th March 2022) - De Luca, Carlotta; Schachner, Anna; Heidl, Sarah; Hess, Michael
Highlights: A chimeric fiber protein was designed merging epitopes from two different FAdV species. The chimeric fiber was able to protect chickens against HHS and IBH. Protection was associated with high antibody response but no neutralizing activity. This is the first subunit vaccine protecting chickens from multiple FAdV diseases. Abstract: In the past decades, fowl adenovirus (FAdV)-related diseases became an increasing concern for the poultry industry worldwide. Various immunization strategies against FAdVs have been experimentally investigated, with a particular focus on subunit vaccines against hepatitis-hydropericardium syndrome (HHS), caused by FAdV serotype 4, and inclusion body hepatitis (IBH), caused by serotypes 2, 8a, 8b and 11. In this study, we extended our innovative concept of recombinant chimeric fiber proteins to design a novel chimera combining epitopes from two distinct serotypes, FAdV-4 and -11, and we investigated its efficacy to simultaneously protect chickens against HHS and IBH. Specific pathogen-free chickens were vaccinated with the novel recombinant chimeric fiber and subsequently challenged with either a HHS- or IBH-causing strain. Vaccinated/challenged birds exhibited a reduction of clinical signs, limited hepatomegaly and lower levels of AST compared to the respective challenge controls. Furthermore, the vaccine prevented atrophy of HHS-affected lymphoid organs, such as thymus and bursa of Fabricius, and viral load in the target organs was significantly reduced. Clinical protection was associated with high levels of pre-challenge antibodies measured on ELISA plates coated with the vaccination antigen. Interestingly, the development of neutralizing antibodies was limited against FAdV-11 and absent against FAdV-4, indicating that protection granted by such an antigen may be linked to different immunization pathways. In conclusion, we proved that the concept of chimeric fiber vaccines can be extended across viral species boundaries and represents the first single-component FAdV subunit vaccine providing comprehensive protection against different FAdV-associated diseases.